Oxidized phospholipids on apoB-100-containing lipoproteins: a biomarker predicting cardiovascular disease and cardiovascular events. (October 2011) - Taleb, Adam; Witztum, Joseph L; Tsimikas, Sotirios
Oxidative stress is a well-known etiologic factor in the development of cardiovascular disease. Oxidation of lipoproteins, and in particular of low density lipoprotein, is a necessary if not obligatory mechanism for the generation of macrophage-derived foam cells, the first major initiating factor in the development of an atherosclerotic plaque. Oxidation of lipoproteins does not result in the generation of a single, defined molecular species, but of a variety of oxidation-specific epitopes, such as oxidized phospholipids and malondialdehyde-lysine epitopes. Unique monoclonal antibodies have been developed to bind these well-defined epitopes, and have been used in in vitro assays to detect them on circulating lipoproteins present in plasma. This article will summarize the accumulating clinical data of one oxidation-specific biomarker, oxidized phospholipids (OxPL) on apoB-100 lipoproteins. Elevated levels of OxPL/apoB predict the presence and progression of coronary, femoral and carotid artery disease, are increased following acute coronary syndromes and percutaneous coronary intervention, and predict the development of death, myocardial infarction, stroke and need for revascularization in unselected populations. OxPL/apoB levels are independent of traditional risk factors and the metabolic syndrome, and enhance the risk prediction of the Framingham Risk Score. The OxPLs measured in this assay reflect the biological activity of the most atherogenic lipoprotein(a) (Lp(a)) particles, reflected in patients with high plasma Lp(a) levels with small apo(a) isoforms. The predictive value of OxPL/apoB is amplified by Lp(a) and phospholipases such as lipoprotein-associated phospholipase A2 and secretory phospholipase A2, which are targets of therapy in clinical trials. This assay has now been validated in over 10, 000 patients and efforts are underway to make it available to the research and clinical communities.